Pengaruh Brand Ambassador, Harga, Dan Kualitas Produk Terhadap Keputusan Pembelian Konsumen Pada Skincare Whitelab (Studi Kasus Pada Mahasiswi Prodi Manajemen FEB Universitas Islam Malang) - Nurul Fitri; N. Rachma; Andi Normaladewi (UNIVERSITAS ISLAM MALANG, 2023)
Abstract This study aims to analyze and determine the effect of brand ambassadors, price, and product quality on consumer purchasing decisions in the Skincare Whitelab study of 2019 FEB UNISMA management study students. The type of research used is explanatory research with a quantitative approach. The research sample was taken by purposive sampling technique with the Malhotra formula used for sampling, namely the number of items x 5 so that the total sample is 100 respondents. The data analysis method used in this study is quantitative data analysis using multiple linear regression analysis. Testing the data carried out is testing the simultaneous hypothesis (Test F) and testing the partial hypothesis (Test t). The results of this study indicate that brand ambassadors, prices, and product quality have a positive and significant effect on consumer purchasing decisions at Skincare Whitelab. Keywords: Brand Ambassador, Price, and Product Quality on Consumer Purchase Decisions at Skincare Whitelab.